George Norris - Kennedy, John F. (John Fitzgerald), 1917-1963 (Social Studies School Service, 1983)
Examines the controversial stand taken by Senator George W. Norris on the Armed Ships Bill when it was submitted to a lame duck Congress by President Wilson. Discusses why Norris stood by his convictions in the face of severe oppsition.